Isoflavones in aglycone solution enhance ultraviolet B‐induced DNA damage repair efficiency. (April 2014) - Iovine, B.; Garofalo, M.; Orefice, M.; Giannini, V.; Gasparri, F.; Monfrecola, G.; Bevilacqua, M. A.
Summary The isoflavones daidzein and genistein are natural compounds which have anti‐inflammatory and photoprotective activities, and may be effective in the repair of ultraviolet (UV)‐induced photodamage. In this study, an alcoholic solution of aglycone isoflavones with a genistein:daidzein ratio of 1:4 [Rottapharm (RPH)‐aglycone] was examined for its effects on the repair of DNA damage induced by a single dose of UVB irradiation (20 mJ/cm2). For this purpose, human skin cells were first UVB‐irradiated and then treated with RPH‐aglycone. Comet assay analysis was used to estimate the UVB‐induced DNA damage at different time points after treatment by measuring the tail moment parameter. We found that treatment with 10 μmol/L RPH‐aglycone solution resulted in a significantly reduced tail moment at 1 h after treatment, and 34–35% enhancement of damage repair at 4 h after treatment. These results suggest that isoflavone aglycones are protective against UVB‐induced DNA damage.